Impact of the Economic Downturn on Elective Lumbar Spine Surgery in the United States: A National Trend Analysis, 2003 to 2013 - Bernstein, David N. (Global Spine J, 2017)
STUDY DESIGN: Retrospective database analysis. OBJECTIVE: The impact of the 2008-2009 economic downtown on elective lumbar spine surgery is unknown. Our objective was to investigate the effect of the economic downturn on the overall trends of elective lumbar spine surgery in the United States. METHODS: The Nationwide Inpatient Sample (NIS) was used in conjunction with US Census and macroeconomic data to determine historical trends. The economic downturn was defined as 2008 to 2009. Codes from the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM), were used in order to identify appropriate procedures. Confidence intervals were determined using subgroup analysis techniques. RESULTS: From 2003 to 2012, there was a 19.8% and 26.1% decrease in the number of lumbar discectomies and laminectomies, respectively. Over the same time period, there was a 56.4% increase in the number of lumbar spinal fusions. The trend of elective lumbar spine surgeries per 100 000 persons in the US population remained consistent from 2008 to 2009. The number of procedures decreased by 4.5% from 2010 to 2011, 7.6% from 2011 to 2012, and 3.1% from 2012 to 2013. The R (2) value between the number of surgeries and the S&P 500 Index was statistically significant (P ≤ .05). CONCLUSIONS: The economic downturn did not affect elective lumbar fusions, which increased in total from 2003 to 2013. The relationship between the S&P 500 Index and surgical trends suggests that during recessions, individuals may utilize other means, such as insurance, to cover procedural costs and reduce out-of-pocket expenditures, accounting for no impact of the economic downturn on surgical trends. These findings can assist multiple stakeholders in better understanding the interconnectedness of macroeconomics, policy, and elective lumbar spine surgery trends.